Exploring the Factors That Influence Students’ Interests in Learning English at Senior High Schoo - Arrasydinda Farra Fannisha (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This thesis investigates the internal and external factors that influence the interest of grade X senior high school students in learning English. Utilizing a quantitative descriptive design, this study aims to fill the gap in existing literature, which has primarily focused on university-level learners or employed correlational and qualitative approaches. The participants consisted of 100 tenth-grade students from a public senior high school in Jember, selected through purposive sampling based on teacher recommendations. Data were collected through a structured questionnaire grounded in Slameto’s theory of learning interest factors, covering both internal (e.g., physical condition, attention, readiness, and intelligence) and external (e.g., family support, school environment, peer influence) dimensions. The results show that both internal and external factors significantly affect students’ interest in learning English. However, internal factors were found to be more dominant, accounting for 53.96% compared to 46.04% of external factors. Key internal influences include physical well-being and readiness, while external influences include teacher support, classroom environment, and peer encouragement. Students reported being more motivated when they were healthy, could clearly hear and see teaching materials, received encouragement from teachers, and had supportive peers. Conversely, lack of parental involvement and insufficient classroom facilities were noted as barriers to engagement. The findings suggest that fostering a conducive learning environment both at school and at home plays a crucial role in enhancing students’ interest in English learning. By identifying the most influential factors, the research offers valuable insight into how students’ interest can be cultivated to support more effective English language acquisition during a critical period of their educational development.
Entry oleh Arif 2026 Maret 16
Keywords: Students; Learning English